Microclimate and regeneration patterns of Polylepis Sericea in a treeline forest of the Venezuelan Andes - Rada R., Fermin J.; García Nuñez, Carlos; Rangel, Sairo (SABER-ULA, 2011)
Tropical high mountains constitute environments where harsh conditions prevail. Polylepis forests are found above the continuous forest line throughout the Andes, with P. sericea as the only species in Venezuela. Sprouting has been described as an effective establishment strategy in environments where disturbance and/or severe conditions exist. Considering establishment stages as filter phases under stressful environments, we studied different aspects of the regeneration of P. sericea: Reproduction type, seeding or sprouting, and their distribution in relation to adult canopies. We also measured different microclimatic conditions under the forest canopies and beyond the forest in order to relate them to Polylepis’ distribution. The largest number of P. sericea individuals occurred in smaller (0-30 cm) size categories. A larger number of plants corresponded to sprouts (56%) during the establishment phase. Seedings occurred more frequently at the edge of the canopies while sprouts were found closer to trunks of adult trees. Establishment of young plants in this particular habitat probably comes down to a compromise between nursing effects by canopies of the adult trees favoring water and temperature conditions and insufficient light limiting photosynthetic processes under the tree canopies. Differences found in reproductive patterns coincide with postulations favoring vegetative regeneration under more extreme conditions.
Microclima y patrones de regeneración de Polylepis Sericea en un bosque del treeline en Los Andes venezolanos
Keywords: Páramo de Mucubají; Altos Andes tropicales; Límite arbóreo; Plántula; Rebrote; Sprouting; Treeline; Tropical high Andes; Seedling; Biología; Revistas